Economic Theory, Economic Reality and Economic Policy - Sorokin, Dmitry Evgenievich (Economy of Regions, 2015)
This paper analyzes the opposition between the «liberals» and «statists» in the Russian political and economic thought. It demonstrates that the economic liberalization is an absolute prerequisite for the transition to sustainable socio-economic development. Such development must rely on investment activities of the state, which in the current circumstances is a necessary but not sufficient measure for reversing the negative trends. The negative developments can be prevented only through implementation, along with the institutional changes in the economic area that form a strata of economically independent entrepreneurs-innovators, of no less profound transformation in political institutions aimed at democratization of public life.